A Comparative Study Between 2 Different Grafts Used as Patches After Plaque Incision and Inflatable Penile Prosthesis Implantation for End-Stage Peyronie's Disease. Issue 6 (9th May 2018) - Falcone, Marco; Preto, Mirko; Ceruti, Carlo; Timpano, Massimiliano; Garaffa, Giulio; Sedigh, Omidreza; Sibona, Mattia; Oderda, Marco; Gontero, Paolo; Rolle, Luigi
Abstract: Background: Although many grafts have been used for plaque incision with grafting (PIG) and penile prosthesis (PP) implantation, there is no evidence that favors 1 specific graft over another. Aim: To compare fibrin-coated collagen fleece (TachoSil; Baxter International, Deerfield, IL, USA) with porcine small intestinal submucosa (SIS; Cook Biotech, West Lafayette, IN, USA) as grafts. Methods: From January 2007 to January 2015, 60 non-randomized consecutive patients affected by end-stage Peyronie disease underwent PIG and PP implantation (AMS 700CX; Boston Scientific, Marlborough, MA, USA). All patients underwent preoperative penile dynamic duplex ultrasound. All procedures were performed by the same surgeon. Patients were divided in 2 different groups according to the graft used to cover the albuginea defect. SIS was used for grafting in 34 patients (group A) and TachoSil was used in 26 patients (group B). Outcomes: Overall hospital stay, operative time, 5-point Likert hematoma scale, visual analog scale, incidence of postoperative complications, and PP mechanical failure were selected as outcome measures. Functional outcomes were assessed through validated questionnaires (International Index of Erectile Function, Erectile Dysfunction Inventory of Treatment Satisfaction, and Sexual Encounter Profile questions 2 and 3) preoperatively and 3, 6, and 12 months postoperatively. Results: The patients' median age was 63 years. No statistically significant differences were detected between groups for age and type and degree of curvature (median = 65°). Average follow-up was 35 months. No major intraoperative complications were reported. The average operative time was 145 minutes for group A and 120 minutes for group B. No statistically significant differences between groups were detected for postoperative complications. Only 3 patients developed a major postoperative complication requiring a 2nd surgical intervention: 1 patient in group A for mechanic failure and 1 patient in group A and 1 in group B for inflatable PP infection. Multivariate statistical analysis showed no significant difference for all variables analyzed between the 2 groups, except for operative time, which was significantly shorter for group B. Clinical Implications: TachoSil could represent a valuable option for grafting, considering its advantages in operative time and cost compared with SIS. Strengths and Limitations: Long-term follow-up represents a strength factor. Main limitations are the non-randomized nature of the study and the small number of patients. Conclusions: TachoSil seems to represent an effective solution for grafting after PIG and PP implantation. However, additional studies are warranted to confirm our results.